Cystitis in pediatric age group and its empirical therapy in a coastal region of southern India - K.L, Shobha; Rao S, Gowrish (International Journal of Medicine, 2023)
Cystitis in childhood, is a common health issue causing morbidity and mortality. This study was to find out the bacterial pathogens causing cystitis in children and its susceptibility pattern. 1792 urine specimens from 1day- 18 years of age suspected of cystitis were obtained. Samples were inoculated into culture plates. Identification of the pathogens was by MALDI-ToF mass spectrometry and antimicrobial susceptibility testing by VITEX 2 system (bioMerieux,Inc, Durham, NC). 48.38% were males and 51.61% were females, 65% attended outpatient department and 35% were admitted in the hospital. Cystitis was more frequently seen in less than one year. Samples when on inoculation into the culture plates, had no organisms in 69.31% and 30.69% had significant bacteriuria. Bacteriuria among boys was more frequently seen in the age group of less than one year of age (35.06%) in the females, bacteriuria was more commonly seen in the age group of 1-5 years (28.32%). Escherichia coli 63.45% was the commonest pathogen isolated. Susceptibility to Trimethoprim/sulphamethoxazole was 84.53% and Ampicillin 45.56% .Since Trimethoprim/sulphamethoxazole is an FDA approved and cost effective drug, it could be an empirical drug of choice for treating cystitis in children of more than 6 weeks of age in the developing countries.